Digital Archive Transformation for Smart Governance: A Four-Pillar Framework for Trustworthy, AI-Ready Digital Government - Dwi Ridho Aulianto (Blockchain, Artificial Intelligence, and Future Research, 2026)
Digital transformation in government often prioritizes visible service channels while neglecting the records infrastructure that establishes evidential integrity, auditability, and institutional memory. This study synthesizes 24 Scopus-indexed journal articles published between 2010 and 2026 to examine how digital archive transformation enables smart governance and to identify its implementation conditions. A qualitative descriptive-analytical review used a reproducible search, screening, thematic coding, and cross-study synthesis. The findings identify four recurrent mechanisms: policy and records governance, interoperable systems and secure technologies, workforce capability, and a data-driven organizational culture. Fragmented applications, inconsistent metadata, uneven competency, governance discontinuity, and change resistance constrain the conversion of service data into trustworthy public records. The study proposes a four-pillar framework that positions electronic records management as the governance layer connecting operational systems with transparency, accountability, and evidence-based decision-making. The framework extends smart-governance research by treating digital archives as active, trustworthy information infrastructure that can be made AI-ready and, where institutionally justified, reinforced through distributed-ledger audit mechanisms.